The Role of Parents in Supporting the Growth and Mental Readiness of the Golden Generation 2045 - Riza Pratiwi Pohan; Zainun Zainun (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to understand how the role of parents contributes to supporting the growth and mental readiness of children as part of efforts to shape the golden generation of 2045, particularly in Sipogu Village, Arse District. The research was conducted using a descriptive qualitative approach, employing in-depth interviews and observations with parents as well as local community leaders. The results of the study indicate that the role of parents is very important in creating an environment that supports the physical, emotional, and intellectual development of children. Forms of support are reflected in the attention given, moral guidance, discipline formation, as well as involvement in both formal and non-formal education. However, there are several challenges still faced, such as parents' limited knowledge about proper parenting patterns and minimal access to information. Therefore, collaboration between families, schools, and the government is a key factor in strengthening the role of parents to prepare children who are resilient, intelligent, and competitive in order to realize the Golden Indonesia 2045.